CHALLENGES IN DESIGNING NANOROBOTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Nanorobotics is the technology to create machines or robots at or near nanometer in size. More specifically, nanorobotics refers to the still hypothetical nanotechnology engineering discipline of designing and building nanorobots. Nanorobots (nanobots, nanoids, or nanites) are devices typically 0.1-10 micrometers in size and constructed of nanoscale or molecular components.